1976
DOI: 10.1002/1097-0142(197611)38:5<1917::aid-cncr2820380508>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Amphotericin B plus 1,3-BIS (2-chloroethyl)-1-nitrosourea (BCNU-NSC NO. 409962) in advanced cancer.Phase I and preliminary phase II results

Abstract: Twenty-one patients with advanced metastatic cancer received amphotericin B (AmB) plus BNUC in a Phase I chemotherapy trial. Of 11 patients with measurable metastases from bronchogenic carcinoma, five had partial antitumor responses lasting 1.5 to 12+ months, and one had objective improvement. Only two of six patients with other types of tumors had objective improvement of short duration. No consistent evidence of immunologic stimulation was observed in eight patients studied. These results suggest that amphot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

1978
1978
1989
1989

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Also, in several lymphoid malignancies in mice, amphotericin B has shown enhanced chemotherapeutic effects. These data have led to clinical trials of amphotericin B as an adjuvant chemotherapy in cancers of lungs and breasts ,…”
Section: Amphotericin Bmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in several lymphoid malignancies in mice, amphotericin B has shown enhanced chemotherapeutic effects. These data have led to clinical trials of amphotericin B as an adjuvant chemotherapy in cancers of lungs and breasts ,…”
Section: Amphotericin Bmentioning
confidence: 99%
“…These data have led to clinical trials of am photericin B as an adjuvant chemotherapy in cancers of lungs and breasts. 54,55 Our laboratory has been studying the interactions in vitro of amphotericin B and common cytotoxic agents in cases of leukemias and malignant melanomas of human beings. These studies suggest there is promise of benefit in malignant melanomas.…”
Section: Chemo-immunotherapymentioning
confidence: 99%
“…As shown in Table 1, in 5 of the 7 cancer cases that received combination therapy, the ratio of the 5-FU content of the cancer tissue to that of the normal tissue surrounding the lesion was higher than the ratio obtained in 4 control cases. Presant et al (1976) reported a combination therapy using AmB and BCNU. Nakazawa et al (1978) reported that an intravenous drip of AmB had promoted the incorporation of neocarzinostatin (NCS) into human gastric tissues.…”
mentioning
confidence: 99%
“…As shown in Table 1, in 4 of the 6 cancer cases that received combination therapy, the NCS titers of the cancer tissues were higher by 10 to 80% than those of the normal tissues surrounding the lesions. Presant et al (1976) reported a combination therapy using AmB and BCNU. Nakazawa et al (1978) reported that an intravenous drip of AmB had promoted the incorporation of NCS into human gastric cancer tissues.…”
mentioning
confidence: 99%